Perancangan Aplikasi Ujian Masuk Karyawan CV.XYZ Menggunakan Metode Waterfall: Array - Irwan, Dedy (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2020)
In receipt of prospective employees who will work on a CV. XYZ spreads the acceptance of prospective employees through print media. Prospective employees will come to CV. XYZ by carrying the file, this causes the prospective applicants to crowded the CV. XYZ thus interferes with office activities. The physical files that will accumulate in the management section of the employee staff will lead to the old file selection process and not to mention the preparation of entrance exam rooms for prospective employees. For that designed entrance exam application for prospective employees. Prospective employees simply register on the website without coming to the CV. XYZ and send the required job application file online. Design this app using waterfall method.